High frequency somatic embryogenesis in cotton - (:unkn) unknown (ACAD SCIENCES CZECH REPUBLIC, INST EXPERIMENTAL BOTANY, 2004)
A highly reproducible system for efficient somatic embryogenesis was developed to regenerate plantlets from cotton ( Gossypium hirsutum L.) cultivars (Nazilli M-503 and Nazilli 143). Shoot apices, hypocotyls and nodes of 10-d-old seedlings were used as explants. High frequency (100%) embryogenic calli was initiated from all tested explants on Murashige and Skoog (1962) (MS) media supplemented with 1 g dm(-3) polyvinylpyrrolidone (PVP), 1 mg dm(-3) 6-benzylaminopurine (BAP), 0.5 mg dm(-3) kinetin for Nazilli M-503 and 1 g dm(-3) PVP, 2 mg dm(-3) BAP, 0.5 mg dm(-3) kinetin for Nazilli-143. Globular stage somatic embryos were produced 4 months after transfer to hormone-free MS medium supplemented with 1 g dm(-3) PVP. Subsequent subculture of globular embryos every 3 weeks on hormone-free MS medium led to the development of torpedo and cotyledonary stage embryos with the frequency of 75 and 83.2% from hypocotyl explants of Nazilli M-503 and Nazilli-143, respectively. Afterwards, mature somatic embryos were isolated and cultured on hormone-free MS medium for germination and development into plantlets. The highest germination frequency (42.9%) for Nazilli M-503 somatic embryos were obtained on hormone-free MS medium after 5 months with hypocotyl explants, whereas germination frequencies of Nazilli-143 embryos from hypocotyl, node and apex explants varied between 22 - 30%.
Keywords: Gossypium hirsutum L.; indirect somatic embryogenesis; hypocotyls; cotyledonary node; apex; GOSSYPIUM-HIRSUTUM-L; PLANT-REGENERATION; SUSPENSION CULTURES; TISSUE; INDUCTION; GENOTYPE; LEAVES; CULTIVARS; EXPLANTS; VARIETY